2022
DOI: 10.3389/fnut.2022.952028
|View full text |Cite
|
Sign up to set email alerts
|

The association between obesity and vitamin D deficiency modifies the progression of kidney disease after ischemia/reperfusion injury

Abstract: Acute kidney injury (AKI) alters renal hemodynamics, leading to tubular injury, activating pathways of inflammation, proliferation, and cell death. The initial damage caused to renal tissue after an ischemia/reperfusion (I/R) injury exerts an important role in the pathogenesis of the course of AKI, as well as in the predisposition to chronic kidney disease. Vitamin D deficiency has been considered a risk factor for kidney disease and it is associated with tubulointerstitial damage, contributing to the progress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
0
0
5

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 93 publications
2
0
0
5
Order By: Relevance
“…Our data demonstrated an increase in EMT in the VitD-de cient diabetic rats. Similar to our ndings, previous studies have also demonstrated that VitD de ciency is related to increased expression of vimentin and α-SMA in tubular and tubulointerstitial cells, respectively, of the rats submitted to a high-fat diet [42] and in rats euthanized 60 days after I/R injury [36]. Increased expression of α-SMA and vimentin may contribute to the accumulation of ECM and consequent tubulointerstitial brosis considered the end common pathway to all progressive kidney diseases and which can culminate in ESRD [40].…”
Section: Discussionsupporting
confidence: 92%
“…Our data demonstrated an increase in EMT in the VitD-de cient diabetic rats. Similar to our ndings, previous studies have also demonstrated that VitD de ciency is related to increased expression of vimentin and α-SMA in tubular and tubulointerstitial cells, respectively, of the rats submitted to a high-fat diet [42] and in rats euthanized 60 days after I/R injury [36]. Increased expression of α-SMA and vimentin may contribute to the accumulation of ECM and consequent tubulointerstitial brosis considered the end common pathway to all progressive kidney diseases and which can culminate in ESRD [40].…”
Section: Discussionsupporting
confidence: 92%
“…Our data demonstrated an increase in EMT in the VitD-deficient diabetic rats. Similar to our findings, previous studies have also demonstrated that VitD deficiency is related to increase expression of vimentin and α-SMA in tubular and tubulointerstitial cells, respectively, of the rats submitted to a high-fat diet [ 43 ] and in rats euthanized sixty days after I/R renal injury [ 38 ]. An increase in the desmin, vimentin and α-SMA expressions may contribute to the accumulation of ECM and consequent glomerulosclerosis and tubulointerstitial fibrosis considered the end common pathway to all progressive kidney diseases and which can culminate in ESRD [ 42 , 44 ].…”
Section: Discussionsupporting
confidence: 91%
“…Portanto, o rim além de principal local de ativação da VitD é também um importante sítio de ação desse hormônio (Manucha, Juncos, 2017;Hu et al, 2019), sendo sua deficiência amplamente relatada na DRC (Holick, 2007;Li, 2010). Nesse sentido, estudos experimentais demonstraram que a deficiência de VitD está relacionada a piora das lesões renais na DRC (Gonçalves et al, 2014;Felício et al, 2016;Bragança et al, 2018;Almeida et al, 2019;Bernardo et al, 2022) e tem sido considerada como um dos potenciais fatores de risco ao desenvolvimento e progressão da ND em pacientes (Felício et al, 2016;Nakashima et al, 2016;Xiao et al, 2016;Felício et al, 2017;Fan et al, 2018). Contudo, os mecanismos relacionados com o efeito da sua deficiência na progressão da lesão renal não foram ainda completamente elucidados.…”
Section: Influência Da Vitamina D Na Estrutura E Na Função Renalunclassified
“…Portanto, a TEM é caracterizada pela repressão de genes relacionados ao fenótipo epitelial, como da E-caderina, de proteínas de junções apertadas e citoqueratinas, e indução da expressão de genes relacionados ao fenótipo mesenquimal, como da Ncaderina, alfa-actina do músculo liso (α-SMA), desmina e vimentina (Essawy et al, 1997;Caja, Tan, 2019). Estudos demonstraram que a deficiência de VitD contribuiu para o aumento da deposição de proteínas de MEC e alteração fenotípica das células túbulointersticiais sugerindo aumento da TEM nos rins de ratos em diferentes modelos de DRC (Gonçalves et al, 2014;Bragança et al, 2018;Bernardo et al, 2022). Contudo, pouco se sabe sobre os mecanismos moleculares pelos quais a deficiência de VitD leva ao desenvolvimento e progressão desse processo durante a fibrose renal.…”
Section: Transição Epitélio-mesenquimal Durante a Nefropatia Diabéticaunclassified
See 1 more Smart Citation